Children's Right to Play - Mary M. Doyle Roche (Journal of Moral Theology, 2018)
Exploring play in the U.S. reveals adult ambivalence about play, the dominance of competitive consumerism in this sphere of children’s lives, and structural injustices that impact who plays and who is left out. The right to play must respond to children as embodied, relational, developing, and spiritual persons; it must have some concrete measures including time, space, access to playthings, and a broad network of guarantors. Thinking about play as participation in the common good and playfulness as a virtue enhances child well-being and adult flourishing. Looking at play through the lens of the common good tradition within Catholic social teaching, with its insistence on the connection between rights and responsibilities, solidarity, and subsidiarity, opens a way to think about play as a form of participation for children and as a virtuous practice of resistance and transformation for all people.